Ethical violations and the publication of journal articles - Anak Agung Sagung Sawitri (Universitas Udayana, 2019)
Since the academic world is the most related to ethical violations above, have all the stakeholders involved in it taken their respective roles? Does the student's supervisor understand ethics and provide guidance to publish student’s research following ethical principles? As a thesis examiner, have these ethical aspects been raised in the student proposal exam? Has the lecturer or researcher done the research and published it according to ethical principles? As a lecturer of research methods, have they provided enough ethical provisions to students? As an official, for example as the head of study programs, deans and chancellors, have they provided adequate space and systems for conducting ethical research? As a journal manager, have the information on the ethical boundaries been disseminated for prospective writers? Every person can take a role to reduce the occurrence of ethical violations and make small changes that will become cumulatively meaningful.